ENGINEERING SOLUTIONS FOR WATER SECURITY IN MOUNTAINOUS AND STEPPE AREAS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In Uzbekistan, water resources are limited, its geographical distribution is very uneven, and the demand for water is growing. The water use efficiency indicator shows the sustainability of water use as an environmental protection and natural resource. This article presents the analysis of engineering solutions for water security in water-scarce areas, where rainwater and snow water are used as an alternative water resource.